KEANEKARAGAMAN JENIS ANGGREK ALAM (Orchidaceae) BERDASARKAN KETINGGIAN TEMPAT DI GUNUNG POTENG CAGAR ALAM RAYA PASI KOTA SINGKAWANG PROVINSI KALIMANTAN BARAT - Sesar, Novita Putri; M, Iskandar A; Manurung, Togar Fernando (Universitas Tanjungpura, 2020)
Natural orchids are one of the flora in Mount Poteng which is included of Raya Pasi Nature Reserve located at Singkawang City, West Kalimantan Province. Orchids have economic value for source of income and be beneficial to ecology that needs to be protected. The altitudes and environmental factors strongly affected the presence of orchid species.The research aims to record the diversity of natural orchids species based on the altitudes place in Mount Poteng. The research was conducted on February 28 until March 28, 2020. This research uses survey method. The research sample was taken using double plots method and to determine sample plots locations is conducted by purposive. The total number of the sample plots is 16 plots and each plot measure 20 by 50 meters. Based on the result of research found 19 species of natural orchids that consist of 348 individuals. The results analysis of the diversity index of orchid species in whole of altitudes at Mount Poteng is 1,338 that is included medium range. The highest species diversity index of 1,300 occurred at altitude of 400-500 m asl and the lowest species diversity index at altitude of 700-725 m asl that is 0,594. Orchid species which found in whole of altitudes is Dendrobium crumenatum. Furthermor, there were found the orchid species on certain heights are Cleisostoma scortechinii, Cordiglottis filiformis, Ludisia discolor, and Phalaenopsis pantherina at altitude of 400-500 m asl and species of Bromheadia finlaysoniana and Pomatocalpa latifolia found at altitude of 700-725 m asl.Keywords: altitudes, mount poteng, orchids, species diversity